Itch in psoriasis: epidemiology, clinical aspects and treatment options - F Prignano; F Ricceri; L Pescitelli; T Lotti (Dove Medical Press, 2009)
F Prignano, F Ricceri, L Pescitelli, T LottiDepartment of Dermatological Sciences, University of Florence,Florence, ItalyBackground: Pruritus is an important symptom in psoriasis vulgaris, may be severe and seriously affect the quality of life of patients, but published data on its frequency and characteristics are limited.Objective: The study objective was to characterize the prevalence of itch in psoriatic patients and the effect of treatment modalities by using a comprehensive itch questionnaire of our own design.Methods: A structured itch questionnaire was given to 90 patients with moderate to severe chronic-plaque psoriasis selected consecutively from the patients visiting the Department of Dermatology of the University of Florence. The questionnaire concerned the areas involved in psoriasis and pruritus, the pruritus characteristics, the worsening and relieving factors and treatment modalities. Itch intensity was reflected by a 10 point visual analog scale (VAS) and the degree of symptoms discriminated between mild (1–3), moderate (4–7) and severe (8–10).Results: Almost 85% of psoriatic patients suffered from itching; the frequency of pruritus was daily and mean intensity by VAS scale was moderate. Presence and intensity of pruritus and body mass index (BMI) were correlated. 40% of patients with pruritus were overweight (BMI > 25 < 30) and 10% obese (BMI > 30). Almost all patients appeared unsatisfied with the available treatment modalities for pruritus in psoriasis. Emollients, topical steroids and calcipotriol cream could relieve pruritus but their effect was temporary. Among the antipsoriatic therapies, phototherapy with narrow band ultraviolet B (nb-UVB) was the most effective treatment in reducing pruritus. Biological therapies, mainly etanercept and efalizumab, proved useful in its control.Conclusions: The questionnaire was a useful tool to characterize itch, and the results might help us to better understand pruritus in psoriasis. The results confirmed the need for a global study of psoriasis with regard to both the cutaneous manifestations and the itch symptom.Keywords: itch, psoriasis, pruritus, epidemiology, phototherapy, etanercept, efalizumab